Characterizing Groundwater Level Response to Precipitation at Multiple Timescales in the Lubei Plain Region Using Transfer Function Analysis - Lewei Xu; Huili Gong; Beibei Chen; Chaofan Zhou; Xueting Zhong; Ziyao Ma; Dexin Meng (Remote Sensing)
Groundwater is essential for ecosystem stability and climate adaptation, with precipitation variations directly affecting groundwater levels (GWLs). Human activities, particularly groundwater exploitation, disrupt the recharge mechanism and the regional water cycle. In this study, we propose a new research framework: On the basis of analyzing the spatiotemporal variability characteristics of precipitation and shallow GWL, we used transfer function analysis (TFA) to quantify the multi-timescale characteristics of precipitation–GWL response under the effects of climate change and human activities. In addition, we evaluated the GWL seasonality and seasonal response while also considering apportionment entropy. We applied this framework to the Lubei Plain (LBP), and the findings indicated the following: (1) Annual precipitation in the LBP decreased from southeast to northwest, with July and August contributing 51.5% of total rainfall; spatial autocorrelation of GWL was high and was influenced by geological conditions and cropland irrigation. (2) The coherence between GWL and precipitation was 0.96 in the high-precipitation areas but was only 0.6 in overexploited areas, and sandy soils enhanced the effective groundwater recharge, with a gain of 1.65 and a lag time of 2.1 months. (3) Over interannual scales, GWL response was driven by precipitation distribution and aquifer characteristics, while shorter timescales (4 months) were significantly affected by human activities, with a longer lag time in overexploited areas, which was nearly 60% longer than areas that were not overexploited. (4) Groundwater exploitation reduced the seasonality of GWL, and irrigation reduced the coherence between GWL and precipitation (0.5), with a gain of approximately 0.5, while a coherence of 0.8 and a gain of 3.5 were observed in the non-irrigation period. This study clarified the multi-timescale characteristics of the precipitation–GWL response, provided a new perspective for regional research on groundwater response issues, and proposed an important basis for the short-term regulation and sustainable development of water resources.